Circulating sST2 and catestatin levels in patients with acute worsening of heart failure: a report from the CATSTAT‐HF study. (18th July 2020) - Borovac, Josip A.; Glavas, Duska; Susilovic Grabovac, Zora; Supe Domic, Daniela; Stanisic, Lada; D'Amario, Domenico; Kwok, Chun S.; Bozic, Josko
Abstract: Aims: Soluble suppression of tumourigenicity 2 (sST2) and catestatin (CST) reflect myocardial fibrosis and sympathetic overactivity during the acute worsening of heart failure (AWHF). We aimed to determine serum levels and associations of sST2 and CST with in‐hospital death as well as the association between sST2 and CST among AWHF patients. Methods and results: A total of 96 AWHF patients were consecutively enrolled, while levels of sST2 and CST were determined and compared between non‐survivors and survivors. Predictive values of sST2 and CST for in‐hospital death were determined by the penalized multivariable Firth logistic regression. The diagnostic ability of sST2 and CST for in‐hospital death was assessed by the receiver operating characteristic analysis and examined with respect to the N‐terminal pro‐brain natriuretic peptide (NT‐proBNP), high‐sensitivity cardiac troponin I, and C‐reactive protein. The in‐hospital death rate was 6.25%. Serum sST2 and CST levels were significantly higher among non‐survivors than survivors [146.6 (inter‐quartile range, IQR 65.9–156.2) vs. 35.3 (IQR 20.6–64.4) ng/mL, P < 0.001, and 19.8 (IQR 9.9–28.0) vs. 5.6 (IQR 3.4–9.8) ng/mL, P < 0.001, respectively]. Both sST2 and CST were independent predictors of in‐hospital death [Firth coefficient (FC) 6.00, 95% confidence interval (CI), 1.48–15.20, P = 0.005, and FC 6.58, 95% CI 1.66–21.78, P = 0.003, respectively], while NT‐proBNP was not a significant predictor (FC 1.57, 95% CI 0.51–3.99, P = 0.142). In classifying non‐survivors from survivors, sST2 provided area under the curve (AUC) of 0.917 (95% CI 0.819–1.000, P < 0.001) followed by CST (AUC 0.905, 95% CI 0.792–1.000, P < 0.001), while NT‐proBNP yielded AUC of 0.735 (95% CI 0.516–0.954, P = 0.036). High‐sensitivity cardiac troponin I and C‐reactive protein were not found as significant classifiers of in‐hospital death (AUC 0.719, 95% CI 0.509–0.930, P = 0.075, and AUC 0.682, 95% CI 0.541–0.822, P = 0.164, respectively). Among survivors, those with sST2 serum levels ≥35 ng/mL had significantly higher CST levels, compared with those with sST2 < 35 ng/mL (9.05 ± 5.17 vs. 5.06 ± 2.76 ng/mL, P < 0.001). Serum sST2 levels positively and independently correlated with CST levels in the whole patient cohort ( β = 0.437, P < 0.001). Conclusions: Elevated sST2 and CST levels, reflecting two distinct pathophysiological pathways in heart failure, might indicate impending clinical deterioration among AWHF patients during hospitalization and facilitate prognosis beyond traditional biomarkers regarding the risk of in‐hospital death (CATSTAT‐HF ClinicalTrials.gov Number NCT03389386).